ПРОБЛЕМИ ІДЕНТИФІКАЦІЇ ОСОБИСТОСТІ В ІНФОРМАЦІЙНОМУ СУСПІЛЬСТВІ - Жидкова, О. О. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 1970)
Аналізуються проблеми ідентифікації особистості, викликані змінам в засобахінформаційної техніки. Особлива увага приділяється розгляду інформаційних технологій, які нелише змінили управління технологічними процесами, але і стали інструментом впливу надіяльність людини.О.О. ЖидковаПРОБЛЕМЫ ИДЕНТИФИКАЦИИ ЛИЧНОСТИ В ИНФОРМАЦИОННОМ ОБЩЕСТВЕАнализируются проблемы идентификации личности, вызванные изменениями, вносимымисредствами информационной техники. Особенное внимание уделяется рассмотрениюинформационных технологий, которые не только изменили управление технологическимипроцессами, но и стали инструментом воздействия на деятельность человека.Ключевые слова: информационное общество, информационные технологии, виртуальнаяреальность, коммуникативная среда, техносфера, идентификация, самоидентификация.O. ZhidkovaPROBLEM IDENTIFICATION OF PERSONALITY IN THE INFORMATION SOCIETYThe problems of identification, due to changes introduced by means of information technology.Particular attention is paid to the information technology, which not only changed the management oftechnological processes, but also became the instrument of influence on human activities.Key words: information society, information technology, virtual reality, communicationenvironment, a technosphere, identification, self-identification.